Interactive Competition Between Individual Diffusion Layers during Cyclic Voltammetry at Random Arrays of Band and Disk Electrodes: A Thorough Analysis Based on Global Simulations. Issue 13 (23rd April 2021) - Pireddu, Giovanni; Svir, Irina; Amatore, Christian; Oleinick, Alexander
Abstract: This work validates a posteriori the use of the theory developed ca. 40 years ago by Amatore and Savéant for regular arrays of electroactive band or disk electrodes. This theory has been profitably used and widely applied in more than 900 research papers for the treatment of the voltammetric responses of arrays of nanoelectroactive objects that were necessarily random by construction. In this work we show that competitive diffusion interaction between the active sites enforce redistribution of individual diffusion layer which homogenize dimensions of the solution volumes 'feeding' each active site. For arrays of nanodisk electrodes, it also validates the corresponding approximation assuming that its voltammetric behavior is to that afforded by identical independent cylindrical unit cells performing in parallel. Abstract : Random arrays are less random than we thought : Diffusion layers tubes linking each individual electrochemically active site to the solution bulk undergo competitive interactions in their fight for the solution volumes 'feeding' each active site. At long enough times for recognizable voltammograms to be observed, these interactions homogenize the individual current densities that govern the overall electrochemical response of the array. This explains why the theory proposed by Amatore and Savéant almost 40 years ago to describe the behavior of regular arrays has always provided quantitatively sound results even for random ones.